2014 IEEE/ION Position, Location and Navigation Symposium - PLANS 2014 2014
DOI: 10.1109/plans.2014.6851408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structural anisotropy on anchor loss mismatch and predicted case drift in future micro-Hemispherical Resonator Gyros

Abstract: The effect of structural anisotropy leading to anchor loss mismatch in micro-Hemispherical Resonator Gyros (micro-HRGs) is investigated by developing an anchor loss model based on finite element analysis. Worst-case lower bound estimates for the anchor loss component of the quality factor (Q) are found based on the computed frequency difference between a clamped support and a free support interface. The Young's modulus of the finite element model is varied in a 4 th -harmonic pattern in the circumferential dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A lower-bound 'worst-case' value of Q due to anchor loss (Q anchor ) can be estimated for each of the modes by assuming that all the strain energy at the interface is dissipated into the substrate (that is, there are no acoustic reflections) 26,27 . However, this condition is only valid when the dimensions of the substrate are much larger than the wavelength of the acoustic wave generated by the resonator, which is rarely true.…”
Section: Mechanical Reduction Of Anisodampingmentioning
confidence: 99%
“…A lower-bound 'worst-case' value of Q due to anchor loss (Q anchor ) can be estimated for each of the modes by assuming that all the strain energy at the interface is dissipated into the substrate (that is, there are no acoustic reflections) 26,27 . However, this condition is only valid when the dimensions of the substrate are much larger than the wavelength of the acoustic wave generated by the resonator, which is rarely true.…”
Section: Mechanical Reduction Of Anisodampingmentioning
confidence: 99%
“…This work confirmed that the anchor geometry has a significant effect on the Q of these types of resonators. Notably, many other works have widely discussed analytical and numerical models in order to predict the anchor loss and Q of different types of resonators [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in fabricating µ-HRGs is the supporting anchor. The height of the support anchor is usually limited by the thickness of the sacrificial layer, which causes large damping [22]. Moreover, the size of the support anchor is usually determined by the etching time of the sacrificial layer, so it cannot be precisely controlled, which limits the accuracy of the µ-HRGs.…”
Section: Introductionmentioning
confidence: 99%